A controversial topic. Teachers evaluation. (Journal of Parents and Teachers, 2013)
To talk about teachers practice evaluation nowadays assumes to refer to one of the most problematic, controversial and feared ambits by a big portion of the teachers.The intention of the article is to encourage teachers to look towards self-evaluation practices that entail the idea of the evaluation as an aid, growing and personal and professional development whose aim is to help the teacher to discover how he/she can improve his/her professional practice.Only by using evaluation as a resource for investigation and education (because evaluation is a way of learning), the dream of a teachers evaluation as a quality guarantee will come true. In order to start-up this process, this article presents a series of orientations and didactic strategies for its functionality.
Keywords: Teachers evaluation. Teachers selfevaluation; teacher training